Imaginarios de lo posible: Una reflexión desde la experiencia en la Universidad Tecnológica de Gutiérrez Zamora, México - Erick Hernández Ferrer (Revista Ciencias y Humanidades)
This article analyzes the imaginaries built and circulated by students at the Technological University of Gutiérrez Zamora, Veracruz (Mexico) during their transition into higher education. This analysis is particularly relevant in the field of educational policy, as before the institution's arrival, opportunities for young people in the region were practically nonexistent due to historical exclusion from this level of education. Using an ethnographic approach, these constructions were identified, resulting in an understanding of the school as a social space where individuals create new horizons aimed at reversing the power relations they have been subjected to.